Constant features in Latin American student movements: an approach based on the Chilean case of 2011 - Donoso Romo, Andrés (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper identifies some constant features, both formal and substantial, among the major student movements in Latin America over the last hundred years: the Chilean in 2011, the Mexican in 1968, the Brazilian in 1968, and the Argentinian in 1918. The objective of this study is accomplished by using as a backbone the description of the fundamental features regarding the demands and achievements of the Chilean movement of 2011, which are contrasted with the events taking place in the other three movements. This exercise, in addition to being original, because most studies dedicated to this type of phenomena are confined to national cases, has increased its importance in finding that in 2018 will be simultaneously commemorated several significant dates. Within these celebrations, integrative interpretations such the ones presented here, will be very well received. It is necessary to specify that this article is methodologically based on a systematic process of content analysis, which was facilitated by a software where the key texts that analyze these movements were included. This strategy led to the conclusion that these movements have a set of shared features, such as the use of similar repertoires of action or the fact that they evidenced a strong concern for extra-university issues.